2022
DOI: 10.19044/esj.2022.v18n25p110
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mergers and Acquisitions Strategies on Financial Performance of Commercial Banks in Kenya

Abstract: The operating environment for commercial banks in Kenya has become very dynamic and highly competitive. The witnessed cases of bank failure and poor financial performance have made commercial banks develop strategies to improve their financial performance, remain competitive, and meet the regulator's compliance requirements. Mergers and Acquisitions Strategies are on the rise as a strategy aimed to alleviate the ailing sector. In light of this, the purpose of this study was to examine the impact on financial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Interest rates on loans may decrease if the merger leads to increased efficiency and competition within the local market. However, if the merger significantly decreases competition, the cost of borrowing may increase as the consolidated bank exploits its market power (Gachigo et al 2022). This observation is supported by Bonaccorsi di Patti and Gobbi (2007), who examined the impact of bank M&As on outstanding credit.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 92%
“…Interest rates on loans may decrease if the merger leads to increased efficiency and competition within the local market. However, if the merger significantly decreases competition, the cost of borrowing may increase as the consolidated bank exploits its market power (Gachigo et al 2022). This observation is supported by Bonaccorsi di Patti and Gobbi (2007), who examined the impact of bank M&As on outstanding credit.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 92%
“…Some studies found that mergers/acquisitions result in the improved financial performance of commercial banks (Ibeji, 2015;Kathali, 2018;Korir, 2006;Ogada et al, 2016;Ombaka&Jagongo;2018;Mwanza, 2016). In other studies, the researchers found that mergers and acquisitions strategies do not influence financial performance (Chesang, 2002;David, 2011;Ochieng, 2006;Marembo, 2012;Muya, 2006;Ndura, 2010). Harney (2011) explained that most recent mergers and acquisitions do not directly show financial performance improvement.…”
Section: Statement Of the Problemmentioning
confidence: 97%
“…For MFIs to thrive and grow, particularly in Nigeria where the microfinance sector is still in its infancy, effective credit risk management practices are crucial. When trying to manage credit risk, MFIs in Nigeria have a variety of challenges, including limited access to credit information, inadequate risk management systems, and minimal legal protections (Gachigo, Ondigo, Aduda, & Onsomu, 2023). Due to the substantial credit risk that MFIs were exposed to, there were a lot of loan defaults, capital losses, and financial instability.…”
Section: Conceptual Reviewmentioning
confidence: 99%